Sensory meat quality, ultimate pH values, blood metabolites and carcass parametersin reindeer (Rangifer tarandus tarandus L.) fed various diets - Wiklund, Eva; Nilsson, Anna; Åhman, Birgitta (Rangifer, 2000)
This investigation was made to study and compare the effects of different diets on sensory meat quality and ultimate pH values in reindeer muscles and to relate stress-induced blood metabolites and carcass parameters to the meat quality traits measured. Altogether 23 female reindeer calves were included in the study. During an adaptation period, all reindeer were allowed free access to a mimicked natural diet containing 80% lichens (lichen diet). On January 28, 8 reindeer (group Cjan) were slaughtered. Five reindeer (group C.Mar) were allowed continuous free access to the lichen diet throughout the experiment. During 8 days, the other reindeer (groups PL and PS) were given the lichen diet, half of the amount offered to the control group, and were then starved for one day. Thereafter, these reindeer were fed 80% commercial reindeer feed (pellets) and either 20% lichens (group PL), or 20% silage (group PS) for 5 weeks. After this, all animals were slaughtered. The average carcass weight and dressing percentage in the group fed commercial reindeer feed and lichens (PL) were higher than in group CMar- Fat registrations were generally higher in groups PL and PS than in the groups Cj2n and CMar- Ultimate pH values in M. triceps brachii and M. longissimus were significantly lower in the group CMST than in PL. The levels of all blood metabolites (urea, ASAT and Cortisol) were generally higher in groups PL and PS than in groups Cja„ and CMEF- NO significant differences were found in any of sensory attributes of the meat (monitored according to ISO standards). The present study shows that muscle and fat depots in reindeer can be improved by feeding a diet based on reindeer pellets but suggests that a feeding period of 35 days might be too short to affect the sensory properties of reindeer meat.